Accumulation and distribution of lead and copper in Avicennia marina and Rhizophora apiculata from Balok mangrove forest, Pahang, Malaysia - Yunus, Kamaruzzaman; Zabri, Rina Sharlinda; John, Akbar; Abdurahman, Siti Waznah (Penerbit UKM, 2011)
Bioaccumulation of lead and Copper in Avicennia marina and Rhizophora apiculata was studied. Samples of leaves, barks and roots were collected from Balok mangrove forest, Pahang. Pb and Cu accumulation was higher in Avicennia marina root tissue compared to bark and leaf but lower than surrounding sediment level. The average concentration of Pb in A. marina leaf, bark, root and sediment was observed to be 5.39 ppm, 3.63 ppm, 18.21 ppm and 23.13 ppm, and average Cu concentration was 4.13 ppm, 4.27 ppm, 4.81 ppm and 12.33 ppm, respectively. R. apiculata also showed higher concentration of Pb and Cu in root tissue compared to bark and leaf tissues but lower than surrounding sediment. The average concentration of Pb in R. apiculata leaf, bark, root and sediment was observed to be 4.30 ppm, 2.97 ppm, 22.45 ppm and 31.23 ppm, respectively. The average Cu concentration was 2.93 ppm, 4.71 ppm, 4.81 ppm and 15.52 ppm, respectively. Results of concentration factors (CF) showed that the accumulation of Pb and Cu was higher in A. marina than in R. apiculata.